Microbial Metabolic Engineering for Biopolymers Production - Regmi, Priti; Bhattarai, Tribikram (Journal of Nepal Biotechnology Association, 2025)
This review delves into microbial engineering strategies for biopolymer production, which is crucial for tackling contemporary environmental challenges. It surveys microbial species capable of synthesizing biopolymers and examines genetic engineering techniques to enhance biopolymer yields. For the genetic manipulation approach, mainly the over-expression of the genes responsible for the production, the downregulation/knock out of competing branches, or the abundant supply of cofactors needed for the reaction are mostly tested, among others. This study provides insights into a few applications of metabolic engineering endeavors towards the production of some biopolymers as for poly-γ-glutamic acid (PGA), polyhydroxyalkanoates (PHAs), starch-based materials, and polylactic acid (PLA). This review highlights the importance of genetic manipulation in optimizing microbial strains and fermentation processes for sustainable biopolymer production.